The Application of The Numbered Heads Together Learning Method to Improve Learning Outcomes in Arabic Vocabulary at Al-Mizan Institute of Modern Islamic Education - Ahmad Ghaisan Fadfad; Samsuri Samsuri; Nasrullah Nasrullah (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
This study is a Classroom Action Research (CAR) consisting of four stages: planning, implementation, observation, and reflection. The research also employs a descriptive approach, illustrating how the learning method is applied in the classroom and the outcomes obtained. Based on the test results from the first cycle, the highest pre-test score was 90, and the lowest was 20, while the highest post-test score was 100, and the lowest was 40. In the second cycle, the highest pre-test score was 65, and the lowest was 25. The highest post-test score was 100, and the lowest was 45. The most decisive results are the average test scores and the normalised gain (N-Gain). In the second cycle, the average pre-test score was 47.5 and increased to 92.7 on the post-test, yielding an average N-Gain of 0.9 and an N-Gain percentage of 87.6%, whereas in the first cycle, the average N-Gain was 0.4 with an N-Gain percentage of 44%. This indicates that the researcher's use of the cooperative learning model "Numbered Heads Together" has been effective, according to the normalised gain (N-Gain) standard. These results demonstrate that the "Numbered Heads Together" cooperative learning model can improve student achievement, particularly in learning Arabic vocabulary.